Film “Sang kyai” (Nasionalisme Islam Nusantara Perspektif Semiotika Roland Barthes) - Erni Zuliana (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
Analysis ofFilm "Sang Kyai" (Islamic Nationalism Nusantara Perspective Semiotics Roland Barthes).One of the fundamental problems underlying the author's take on this study, becauseas long as it has begun to wear off Indonesia citizen nationalism stance. Such is the case, the tendency of citizens that Indonesia is more loved by the people of the West,dressing style that follows the culture of people of the West,so this leads to a lack of respectcopyright, the initiative of the Indonesian nation.Another unique phenomenon is when a writer tries to analyze many among small children who haven't cultivated an attitude of nationalism or patriotismby their parents this is evident from the songs the children sing a lot of them sing songs welcoming love of the opposite sexeven more deadly many of them don't know the national anthem of the Republic of Indonesia.The author tried to examine this film in the perspective of semiotics Roland Barthes.According to Roland Barthes there are three meanings in the study of semiotics are denotation, connotation and mitos. By formulating a problem formulation is; How can the representation of Islamic Nationalism signs nusantara which is contained in the film "Sang Kyai". This research uses qualitative research using type approach figure KH Hasyim Ash'ari as the driving force of Nahdhatul Ulama (NU) and the founder of the first cottage Tebuireng Jombang. In this study the author uses the analysis of semiotics Roland Barthes, a theory of semiotics examines about signs. The study in this research is the study of linguistic,language is a system of sound arbitrer coat of arms,used by members of a community to work together,interact, and identifyWhile the studies related to the science of signs as well as very useful once semiotik in studies of languagebecause with through signs everything can be interpreted.As for the results of this study indicate that Islamic Nationalism in the movie "Sang Kyai" perspective of semiotics Roland Barthes can be categorized into three are;(1) maintaining the unity and the unity of the country that is described in the corpus of 1, 2 and 3, (2)Cultivating Shura (consultation), which elaborated on the bodies of 4, 5 and 6,(3) the fight for Justice that is described in the corpus 7 and 8.